The Halloween candy mystery - Markham, Marion M.; McCully, Emily Arnold (Boston : Houghton Mifflin, 1982)
Twins Mickey and Kate use their powers of deduction and scientific expertise to catch a burglar on Halloween night.
Keywords: Mystery and detective stories; Halloween -- Fiction; Twins -- Fiction; Mystery and detective stories; Halloween -- Fiction; Twins -- Fiction